1990
DOI: 10.3168/jds.s0022-0302(90)78729-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Response of Dairy Cows Receiving Bovine Somatotropin via Daily Injections or in a Sustained-Release Vehicle

Abstract: Three experiments were conducted to characterize metabolic and milk production responses of dairy cows receiving recombinantly derived bovine somatotropin administered either by daily injection or in a sustained-release vehicle. In Experiment 1, somatotropin (25 mg/d) purified by two methods was given by daily injection for 14 d and resulted in 3.5 and 3.8 kg/d more milk than controls. Percentages of fat and total solids in milk were also increased by somatotropin. Eleven hematology indices and 12 metabolites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…The prolonged interval of negative EB delayed replenishment of body reserves, because BFT did not increase as quickly after the nadir in bST-treated cows. Although bST reduced BW and BCS, differences between overall treatment means were small and comparable with previous reports (McGuffey et al, 1990). Dohoo et al (2003) estimated that 200 d of bST administration reduced BCS by approximately 0.2 units, and we detected a comparable 0.25 ± 0.09-unit reduction.…”
Section: Dmi and Estimated Energy And Mp Balancesupporting
confidence: 90%
“…The prolonged interval of negative EB delayed replenishment of body reserves, because BFT did not increase as quickly after the nadir in bST-treated cows. Although bST reduced BW and BCS, differences between overall treatment means were small and comparable with previous reports (McGuffey et al, 1990). Dohoo et al (2003) estimated that 200 d of bST administration reduced BCS by approximately 0.2 units, and we detected a comparable 0.25 ± 0.09-unit reduction.…”
Section: Dmi and Estimated Energy And Mp Balancesupporting
confidence: 90%
“…This was a similar level of response to that obtained with a similar bST preparation in concentrate-fed cows (Oldenbroek et al 1989;McGuffey et al 1991). The study reported below was carried out with a sustained release preparation of bST (Somidobove, at two doses) as used in other trials (Oldenbroek et al 1989;McGuffey et al 1990McGuffey et al , 1991Valentine et al 1990). As well as determining responses in yield and composition, parameters of animal health, including maintenance and success of pregnancy and subsequent animal performance, were also examined.…”
Section: Introductionmentioning
confidence: 67%
“…In another study by McShane et al, [39] a slight lowering of urea concentration at 2, 3 and 4th week of bST treatment was observed. In contrast, Annexstad et al, [44] and McGuffey et al, [45] determined slight higher serum urea in dairy cow after administration of rbST. Limited information is available about the effects of rbST on proteins metabolism of domestic animals than for either lipid or carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 89%